2014
DOI: 10.1186/2040-2392-5-9
|View full text |Cite
|
Sign up to set email alerts
|

Engrailed2 modulates cerebellar granule neuron precursor proliferation, differentiation and insulin-like growth factor 1 signaling during postnatal development

Abstract: BackgroundThe homeobox transcription factor Engrailed2 (En2) has been studied extensively in neurodevelopment, particularly in the midbrain/hindbrain region and cerebellum, where it exhibits dynamic patterns of expression and regulates cell patterning and morphogenesis. Because of its roles in regulating cerebellar development and evidence of cerebellar pathology in autism spectrum disorder (ASD), we previously examined an ENGRAILED2 association and found evidence to support EN2 as a susceptibility gene, a fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 114 publications
2
18
0
Order By: Relevance
“…Cerebellar granular neuron cultures from B6/C57 mice at PNDs 5–8 were adapted from previously describe protocols (Rossman et al, ). Briefly, three to six cerebella were cleaned, dissociated by 3‐min treatment with trypsin‐DNase (1% trypsin, 0.1% DNase, Worthington, Lakewood, NJ), and triturated in DNase solution (0.05% in DMEM).…”
Section: Methodsmentioning
confidence: 99%
“…Cerebellar granular neuron cultures from B6/C57 mice at PNDs 5–8 were adapted from previously describe protocols (Rossman et al, ). Briefly, three to six cerebella were cleaned, dissociated by 3‐min treatment with trypsin‐DNase (1% trypsin, 0.1% DNase, Worthington, Lakewood, NJ), and triturated in DNase solution (0.05% in DMEM).…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in the En genes affect the ventral mid-hindbrain nuclei, the locus coeruleus (LC) and the raphe nuclei (RN), ultimately resulting in abnormal levels of norepinephrine (NE) and serotonin (5HT) in forebrain and hindbrain areas during development [37][38][39]. Mice with a deletion of the En2 gene from birth (En2 -/-) demonstrate severe cerebellar hypoplasia, reduced Purkinje cell numbers, disruptions in cerebellar patterning and foliation, reduced hippocampal weight, increased dentate gyrus cell turnover, and an anterior shift in the position of the amygdala nuclei [24,33,[40][41][42][43][44][45][46][47][48]. From a behavioral standpoint, juvenile En2 -/mice, compared with wild-type (WT, En2 +/+ ) mice, display impaired social interaction, memory deficits, improper sensory-motor gating, decreased play, reduced social sniffing, reduced aggressiveness, and depression-related behaviors [24,33,41,[43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…These findings led to a focus on the contribution of the cerebellum to nonmotor cognitive functions [Fatemi et al, ; Strick, Dum, & Fiez, ]. The identification of autism risk genes, such as En2 (Engrailed homeobox 2) [James, Shpyleva, Melnyk, Pavliv, & Pogribny, ] and Met (Met proto‐oncogene) [Abrahams & Geschwind, ; Rossman et al, ; Schaaf & Zoghbi, ] known to be involved in the development of the cerebellum and hindbrain suggested that the emphasis should shift from theories espousing localized dysfunction of the cerebellum to the investigation of mechanisms of hind brain and forebrain development and of the widely distributed circuitry interconnecting them [Fatemi et al, ; Rogers et al, ]. These mechanisms are not yet well delineated.…”
Section: Introductionmentioning
confidence: 99%